Assessment of knowledge of midwives about the scope of professional responsibility under the amended provisions of law - Belowska, Jarosława; Dykowska, Grażyna; Sienkiewicz, Zofia; Gotlib, Joanna (Polish Journal of Public Health, 2014)
Introduction. To work safely, knowledge of law is crucial for midwives who should be familiar with the midwife’s rights and duties as well as their professional responsibility.Aim. Assessment of knowledge of midwives about their professional responsibility.Material and methods. A total of 103 MA Midwifery students of the Medical University of Warsaw, including 55 working and 48 not working as midwives. A diagnostic poll, original anonymous questionnaire, 25 close-ended questions, 8 openended questions. Statistical analysis: STATISTICA 10.0, Mann-Whitney U test, p